Identifikasi Mikroorganisme dari Tempe Khas Bayung Lencir dengan Media PDA - Teuku Daffa Hasian; Ardi Mustakim (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Tempeh, as one of Indonesia's traditional fermented foods, plays a vital role in providing affordable vegetable protein and contains various essential nutrients such as vitamin B12, folic acid, and fiber. Tempeh's uniqueness lies in the fermentation process involving local microorganisms that thrive in soybeans. Tempeh from Bayung Lencir, South Sumatra, is known for its traditional production process, which uses no starter culture. This results in a unique microbiota that has not been widely studied during fermentation. Therefore, this study focused on identifying the microorganisms involved in the tempeh fermentation process. The results showed that Rhizopus oligosporus is the primary microorganism responsible for the formation of tempeh's texture and increasing its nutritional value through the production of proteolytic and lipolytic enzymes that aid in the digestion of protein and fat. Furthermore, lactic acid bacteria such as Lactobacillus plantarum and Pediococcus spp. play a crucial role in creating a more acidic environment, thereby reducing the risk of pathogenic microorganism growth and maintaining product safety. However, an uncontrolled fermentation process can also result in contamination by harmful microorganisms, such as Aspergillus niger and Penicillium spp., which can affect the quality of tempeh and potentially produce mycotoxins that are harmful to health. The use of PDA media has proven effective in isolating and observing the morphological characteristics of fungi, such as colony color, texture, and growth rate. This medium provides adequate results in identifying microorganisms involved in the tempeh fermentation process. This research is important for maintaining the quality and safety of Bayung Lencir's signature tempeh and opens up opportunities for the development of local starter cultures that can improve quality control during the fermentation process. Molecular-based research is needed to further explore the identity of microbes and to improve the safety and competitiveness of tempeh in the global market.